The development reader (London Routledge, 2008)
Comprising writings ordered around intentional and imminent ?development?, this reader offers a compendium of classical and contemporary debates on development: Adam Smith and Karl Marx meet, among others, Robert Wade, Amartya Sen and Jeffrey Sachs.
Includes bibliographical references and index.
Keywords: Development